The Destruction and Reconstruction of North Korea, 1950 - 1960 - Charles Armstrong (Japan Focus)
This article is part of an ongoing series at The Asia-Pacific Journal commemorating the sixtieth anniversary of the start of the US-Korean War.The Korean War, a "limited war" for the US and UN forces, was for Koreans a total war. The human and material resources of North and South Korea were used to their utmost. The physical destruction and loss of life on both sides was almost beyond comprehension, but the North suffered the greater damage, due to American saturation bombing and the scorched-earth policy of the retreating UN forces.1 The US Air Force estimated that North Korea's destruction was proportionately greater than that of Japan in the Second World War, where the US had turned 64 major cities to rubble and used the atomic bomb to destroy two others. American planes dropped 635,000 tons of bombs on Korea -- that is, essentially on North Korea --including 32,557 tons of napalm, compared to 503,000 tons of bombs dropped in the entire Pacific theatre of World War II.2 The number of Korean dead, injured or missing by war's end approached three million, ten percent of the overall population. The majority of those killed were in the North, which had half of the population of the South; although the DPRK does not have official figures, possibly twelve to fifteen percent of the population was killed in the war, a figure close to or surpassing the proportion of Soviet citizens killed in World War II.This article assesses both the destruction and the reconstruction of North Korea in the 1950s.